Constructing Persona and Identity in Charli XCX’s Brat Album - Eny Suprihandani; Ikhwan Muslim; Abdulloh Abdulloh; Riscky Wirayudha (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
This study examines how Charli XCX constructs and performs persona and identity in her 2024 album Brat. In contemporary pop music, persona functions as a performative self that mediates between an artist’s private identity and public image. While previous studies have explored musical persona and identity in popular music, limited attention has been given to the analysis of a full hyperpop album that integrates lyrics, vocal delivery, and production as a cohesive character construction. Addressing this gap, this research aims to analyze (1) how persona and identity are constructed in Brat, (2) the recurring emotional and character traits that define Charli XCX’s performed self, and (3) how the album reflects her identity in relation to themes of fame, vulnerability, and digital culture. Using a qualitative method, the study applies textual and interpretive analysis to all fifteen tracks of Brat, treating the album as a cultural text. The findings reveal that Charli XCX presents a fluid and shifting persona that oscillates between confidence, rebellion, insecurity, and emotional fragility. These traits are reinforced through minimalist lyrics, varied vocal performances, and experimental electronic production. The study concludes that Brat functions as both a personal and performative work, demonstrating how contemporary pop albums serve as spaces for identity construction through sound, voice, and cultural expression